Antiviral effect of multipurpose contact lens disinfecting solutions against coronavirus. Issue 5 (October 2022) - Yasir, Muhammad; Kumar Vijay, Ajay; Willcox, Mark
Abstract: Purpose: To evaluate the antiviral potential of five multipurpose disinfecting solutions against coronavirus (mouse hepatitis virus, a surrogate for SARS-CoV-2 human corona virus). Methods: Test solutions (Biotrue, renu Advanced [Bausch and Lomb], ACUVUE RevitaLens [Johnson and Johnson Vision], cleadew [Ophtecs corp.] or AOSept Plus [Alcon]) were mixed with the coronavirus mouse hepatitis virus at 10 4 plaque forming units (PFU)/mL as the final concentration and incubated at room temperature for the specified disinfection time. Surviving virus from each sample was then quantified by standard plaque forming unit assay and the reduction of PFU for each disinfectant was compared to the phosphate buffer saline (PBS) treated negative control. A regimen test was also conducted using Biotrue. Results: The three multipurpose disinfecting solutions Biotrue (containing PHMB and polyquaternium-1), renu Advanced (PHMB, polyquaternium-1 and alexidine) and ACUVUE RevitaLens (polyquaternium-1 and alexidine) did not kill the coronavirus at the manufacturers recommended disinfection time in the stand alone test. After treatment, the virus's titer (3.8 ± 0.2 log10 for Biotrue, 3.7 ± 0.1 log10 for renu and 3.7 ± 0.2 log10 for RevitaLens) was similar to the negative control (3.7 ± 0.1 log10 ; p ≥ 0.996). AOSept Plus (hydrogen peroxide) and cleadew (povidone iodine) significantly (p < 0.001) reduced the numbers of coronaviruses to below the detection limit (i.e. killed 3.7 ± 0.1 log10 viruses compared to control). However, there was a significant reduction (p = 0.028) in numbers of coronaviruses attached to lenses when using the regimen test with Biotrue. Conclusions: This study shows that oxidative contact lens disinfecting solutions (i.e. those containing povidone-iodine or hydrogen peroxide) provide superior antiviral activity against a coronavirus surrogate of SARS-CoV-2, unless the full regimen test (rub, rinse, disinfect) is used.